Effectiveness and Durability of mRNA Vaccine-Induced SARS-CoV-2-Specific Humoral and Cellular Immunity in Severe Asthma Patients on Biological Therapy - Podrazil, Michal; Taborska, Pavla; Stakheev, Dmitry; Rataj, Michal; Lastovicka, Jan; Vlachova, Alena; Pohunek, Petr; Bartunkova, Jirina; Smrz, Daniel (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) vaccines effectively elicit humoral and cellular immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in healthy populations. This immunity decreases several months after vaccination. However, the efficacy of vaccine-induced immunity and its durability in patients with severe asthma on biological therapy are unknown. In this study, we evaluated the effectiveness and durability of mRNA vaccine-induced SARS-CoV-2-specific humoral and cellular immunity in severe asthma patients on biological therapy. The study included 34 patients with severe asthma treated with anti-IgE (omalizumab, n=17), anti-IL5 (mepolizumab, n=13; reslizumab, n=3), or anti-IL5R (benralizumab, n=1) biological therapy. All patients were vaccinated with two doses of the BNT162b2 mRNA vaccine with a 6-week interval between the doses. We found that this COVID-19 vaccination regimen elicited SARS-CoV-2-specific humoral and cellular immunity, which had significantly declined 6 months after receipt of the second dose of the vaccine. The type of biological treatment did not affect vaccine-elicited immunity. However, patient age negatively impacted the vaccine-induced humoral response. On the other hand, no such age-related impact on vaccine-elicited cellular immunity was observed. Our findings show that treatment of patients with severe asthma with biological therapy does not compromise the effectiveness or durability of COVID-19 vaccine-induced immunity.